3D 1T‐MoS2/CoS2 Heterostructure via Interface Engineering for Ultrafast Hydrogen Evolution Reaction. Issue 33 (19th July 2020) - Feng, Yangyang; Zhang, Ting; Zhang, Jiahui; Fan, Hao; He, Cheng; Song, Jiangxuan
Abstract: Metallic phase (1T) MoS2 has been regarded as an appealing material for hydrogen evolution reaction. In this work, a novel interface‐induced strategy is reported to achieve stable and high‐percentage 1T MoS2 through highly active 1T‐MoS2 /CoS2 hetero‐nanostructure. Herein, a large number of heterointerfaces can be obtained by interlinked 1T‐MoS2 and CoS2 nanosheets in situ grown from the molybdate cobalt oxide nanorod under moderate conditions. Owing to the strong interaction between MoS2 and CoS2, high‐percentage of metallic‐phase (1T) MoS2 of 76.6% can be achieved, leading to high electroconductivity and abundant active sites compared to 2H MoS2 . Furthermore, the interlinked MoS2 and CoS2 nanosheets can effectively disperse the nanosheets so as to enlarge the exposed active surface area. The near zero free energy of hydrogen adsorption at the heterointerface can also be achieved, indicating the fast kinetics and excellent catalytic activity induced by heterojunction. Therefore, when applied in hydrogen evolution reaction (HER), 1T‐MoS2 /CoS2 heterostructure delivers low overpotential of 71 and 26 mV at the current density of 10 mA cm −2 with low Tafel slops of 60 and 43 mV dec −1, respectively in alkaline and acidic conditions. Abstract : A novel interface‐induced strategy is reported to achieve stable and high‐percentage 1T MoS2 by modifying the intrinsic electronic/phase structure at the heterointerface of 1T‐MoS2 /CoS2 . Owing to the high electroconductivity, largely exposed active surface area and excellent structural stability, 1T‐MoS2 /CoS2, with the near zero Gibbs free‐energy, exhibits outstanding electrocatalytic properties for hydrogen evolution reaction (HER) in both alkaline and acidic electrolytes.